MSMEs Upgrade with The Concept of Green Accounting and Digitalization (Study Literature Review) - Kurnia Sari, Ayu; Kesuma, Sambas Ade; Muda, Iskandar (Ridwan Institute, 2023)
MSME is one of the products belonging to the small and environmentally friendly industrial sector. The concept of MSMEs related to green accounting and digitization is still not optimal, so this can be used as research. The purpose of this research is to see how the concept of green accounting and digitization of accounting for MSMEs is developing. To show macro and micro perspectives on green accounting, an issue related to the environment and ecological science, and the sustainable management of natural ecosystems. This research method was carried out using the study literature review method. The population used is 1,603 units of the MSME sector in the city of Medan. The results of this study state that SMEs will be able to upgrade to a high level by applying digitalization to their market place and the concept of green accounting which can provide income for the environment and MSMEs.